HUBUNGAN KEADAAN J ARINGAN PERIODONTAL DENGAN USIA PASA LANSIA DI BANJAR DUKUH SARI SESETAN DENPASAR TAHUN 2016 - Ni Made Sirat; Tridara Adeafrilina (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2017)
Periodontal disease is a disease that affects the tooth supporting tissue, namely gingiva / gum and periodontal tissue, which is the network that connects the teeth and the supporting bone of the tooth, namely the alveolar bone. The prevalence of periodontal disease in all age groups in Indonesia is 96.58%. Research conducted by Tridara Adeafrilina of 40 elderly people of varying ages in Banjar Dukuh Sari, Sesetan Village, South Denpasar in 2016, concluded that almost all respondents experienced periodontal abnormalities. The purpose of this study was to determine the relationship between the condition of periodontal tissue with the age of the elderly in Banjar Dukuh Sari, Sesetan Village, South Denpasar in 2016. This type of cross sectional study, uses secondary data from Tridara Adeafrilina research. Correlation test results obtained sig .: 0, 0.123. The conclusion is that there is no relationship between the age variable with the variable state of the elderly periodontal tissue in Banjar Dukuh Sari after 2016.